Antibiotics prescribing pattern in the in-patient departments of a tertiary care hospital - Ambili Remesh; Samna Salim; A M Gayathri; Uma Nair; K G Retnavally (Archives of Global Professionals, 2013)
Context: Antibiotic prescribing by physicians has gained due importance across the globe, mainly because of an increase in antibiotic usage, prevalence of infections, and drug resistances. Aims: The present study aimed to evaluate the prescribing pattern of antibiotics, their adherence to essential medicines list, disease conditions for which they were prescribed, and their adverse effects. Settings and Design: A cross-sectional prospective study was carried out in six inpatients departments (Surgery, Orthopedics, ENT, Ophthalmology, Medicine, and Pediatrics) of a 550-bed tertiary care hospital in Trivandrum, India for two months (July-August 2012). Institutional Research and Ethics Committee clearance were obtained prior to the study. Materials and Methods: The data were collected in a predesigned performa from the medical case sheets, drug charts, and laboratory investigations of 100 in-patients. The enrolled patients were observed from admission till discharge. Descriptive statistics were applied to the collected data and analyzed using Microsoft Excel software. Results: The mean duration of hospitalization among the study population was 5.48 (±4.28) days. Of the 410 medicines prescribed, antibiotics contributed 151 (36.8%). They were mostly indicated for respiratory infections, and the most common antibiotic was Beta-lactams (91 (60.2%). Interestingly, 89 antibiotics (60%) were administered as injections. About 70 (46%) of the antibiotics were prescribed without any combinations. The adherences to World Health Organization's essential medicines list were 122 (81%). A total of seven adverse drug reactions were reported in the current study. Of which, none were serious, and five (70%) were cutaneous reactions. Conclusions: Of the 100 patients analyzed from six in-patient departments, it was observed that the hospital physicians prescribed antibiotics more rationally with no banned drugs and less newer drugs. Rational prescribing of antibiotics would help avoid polypharmacy and prevent drug resistances.